Binders for sodium-ion batteries: progress, challenges and strategies. Issue 93 (2nd November 2021) - Li, Rong-Rong; Yang, Zhuo; He, Xiang-Xi; Liu, Xiao-Hao; Zhang, Hang; Gao, Yun; Qiao, Yun; Li, Li; Chou, Shu-Lei
Abstract : The challenges faced by binders can be addressed by enhancing the mechanical and chemical bonding strength, designing multifunctional integrated binders, and combining advanced characterization techniques. Abstract : Binders as a bridge in electrodes can bring various components together thus guaranteeing the integrity of electrodes and electronic contact during battery cycling. In this review, we summarize the recent progress of traditional binders and novel binders in the different electrodes of SIBs. The challenges faced by binders in terms of bond strength, wettability, thermal stability, conductivity, cost, and environment are also discussed in details. Correspondingly, the designing principle and advanced strategies of future research on SIB binders are also provided. Moreover, a general conclusion and perspective on the development of binder design for SIBs in the future are presented.